2021
DOI: 10.1038/s41597-021-00954-3
|View full text |Cite
|
Sign up to set email alerts
|

Charge and discharge profiles of repurposed LiFePO4 batteries based on the UL 1974 standard

Abstract: Owing to the popularization of electric vehicles worldwide and the development of renewable energy supply, Li-ion batteries are widely used from small-scale personal mobile products to large-scale energy storage systems. Recently, the number of retired power batteries has largely increased, causing environmental protection threats and waste of resources. Since most of the retired power batteries still possess about 80% of their initial capacity, their second use becomes a possible route to solve the emergent p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…They can be repurposed once again, serving as the battery modules in the energy storage system [78][79][80][81][82]. Governments have noticed this serious problem and are prepared to launch policies to deal with the recovery and reuse of repurposing batteries [79,[83][84][85][86][87]. The discovery of graphene and more low-dimensional materials (such as 1D finite-width GNRs discussed in this work) [88,89] makes scientists believe that these materials can be potential additives in battery materials to improve battery performance and to overcome the recycling problems of Li-ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…They can be repurposed once again, serving as the battery modules in the energy storage system [78][79][80][81][82]. Governments have noticed this serious problem and are prepared to launch policies to deal with the recovery and reuse of repurposing batteries [79,[83][84][85][86][87]. The discovery of graphene and more low-dimensional materials (such as 1D finite-width GNRs discussed in this work) [88,89] makes scientists believe that these materials can be potential additives in battery materials to improve battery performance and to overcome the recycling problems of Li-ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…The technical procedures for evaluating the cells are rarely published in the literature. Except for Chung, Schneider, and Zhao (Chung, 2021;Schneider et al, 2014Schneider et al, , 2009Zhao, 2017). Overall, their technical procedures can be described as follows:…”
Section: Technical Proceduresmentioning
confidence: 99%
“…In real-world applications, the design, form factor, and raw materials of the existing pack/modules/cells often vary greatly from one another, making it difficult to develop a unified technical procedure. Furthermore, information on the detailed technical procedures used is often not easily available in the open literature, except for Schneider et al, who reported the procedure to classification and reuse small cylindrical NiMH battery modules for mobile phones [176,177]; Zhao, who shared the successful experiences of some grid-oriented applications of EV Li-ion batteries in China in a comprehensive technical procedure [178]; and Chung, who announced the procedure described in UL 1974 on LFP repurposing batteries and released the related experimental dataset publicly [179]. Based on the information from these studies, a conceptual procedure for repurposing applications is summarized in five primary steps: (1) judgment of the retired battery system based on historical information, (2) disassembly of retired battery packs/modules, (3) battery performance evaluation (mechanical, electrochemical, and safety), (4) sorting, and (5) developing control and management strategies for repurposing applications.…”
Section: Outlook Of Na-ion Batteriesmentioning
confidence: 99%